Development and physico-chemical analysis of granola formulated with puffed glutinous rice and selected dried Sunnah foods - Agbaje R.; Hassan C.Z.; Norlelawati A.; Abdul Rahman A.; Huda-Faujan N. (Universiti Putra Malaysia, 2024)
Indexed by WOS/ Scopus